(untitled) (jornal of the libyan geographical society, 2009)
The tourism industry is an equation whose first side comprises the available resources, both natural and human, and whose second side is the tourist. Just as tourism cannot exist without natural attractions enhanced by human resources, it is similarly impossible for tourism to succeed without tourists. However, those who design tourism programs often overlook the role of tourists. When preparing tourist programs, they emphasize the presence of all natural and human resources, even those that are not available, in their programs, in an effort to entice and attract tourists. Despite what has been written about the tourism industry, its concept, types, and components, most researchers have overlooked the role of the tourist in promoting the tourism industry, in terms of his requirements and desires, and in terms of his resources, capabilities, and trends. This has led the tourism planner to assume, on behalf of the tourist, his needs and how to satisfy them, based on the available tourism components. Assuming that he is able to attract tourists through his various means, he ignores the fact that the tourist’s mental map is the basis upon which his decisions, preferences, and consequently his behavior depend.